A phase I study of cediranib in combination with cilengitide in patients with recurrent glioblastoma. Issue 10 (24th May 2015) - Gerstner, Elizabeth R.; Ye, Xiaobu; Duda, Dan G.; Levine, Michael A.; Mikkelsen, Tom; Kaley, Thomas J.; Olson, Jeffrey J.; Nabors, Burt L.; Ahluwalia, Manmeet S.; Wen, Patrick Y.; Jain, Rakesh K.; Batchelor, Tracy T.; et al.
Abstract: Background: Despite being a highly vascularized tumor, glioblastoma response to anti-vascular endothelial growth factor (VEGF) therapy is transient, possibly because of tumor co-option of preexisting blood vessels and infiltration into surrounding brain. Integrins, which are upregulated after VEGF inhibition, may play a critical role in this resistance mechanism. We designed a study of cediranib, a vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitor, combined with cilengitide, an integrin inhibitor. Methods: This phase I study was conducted through the Adult Brain Tumor Consortium in patients with recurrent glioblastoma. Once the maximum tolerated dose was determined, 40 patients enrolled in a dose expansion cohort with 20 being exposed to anti-VEGF therapy and 20 being naive. The primary endpoint was safety. Secondary endpoints included overall survival, proportion of participants alive and progression free at 6 months, radiographic response, and exploratory analyses of physiological imaging and blood biomarkers. Results: Forty-five patients enrolled, and no dose toxicities were observed at a dose of cediranib 30 mg daily and cilengitide 2000 mg twice weekly. Complete response was seen in 2 participants, partial response in 2, stable disease in 13, and progression in 21; 7 participants were not evaluable. Median overall survival was 6.5 months, median progression-free survival was 1.9 months, and progression-free survival at 6 months was 4.4%. Plasma-soluble VEGFR2 decreased with treatment and placental growth factor, carbonic anhydrase IX, and SDF1α, and cerebral blood flow increased. Conclusions: The combination of cediranib with cilengitide was well tolerated and associated with changes in pharmacodynamic blood and imaging biomarkers. However, the survival and response rates do not warrant further development of this combination.